1994
DOI: 10.2220/biomedres.15.127
|View full text |Cite
|
Sign up to set email alerts
|

<b>Detection of inducible prostaglandin H synthase-2 in cells in the exudate of rat carrageenin-induced </b><b>pleurisy </b>

Abstract: Pleurisy was induced in rats by intrapleural injection of 0.2 ml of 2% /l-carrageenin. Prostaglandin H synthase (PGHS)-2 was detected using immunoblot analysis in cells of the pleural exudate 5 h after carrageenin injection, and waned at 19 h. PGHS-1 was also detected, but was maintained at similar levels in cells before and after carrageenin injection. The level of PGHS-2 was markedly suppressed by pretreatment of rats with anti-inflammatory dose of dexam ethasone (3 mg/ kg, i.p.) 2 h before carrageenin injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Western blot analysis of the COX isoforms of pleu ral exudate cells was performed by methods described previously [3]. In brief, the frozen cell pellet was …”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis of the COX isoforms of pleu ral exudate cells was performed by methods described previously [3]. In brief, the frozen cell pellet was …”
Section: Western Blot Analysismentioning
confidence: 99%
“…The expression of COX-2 is induced by inflammatory mediators and is suppressed by anti-inflammatory steroids [1], For this reason, COX-2 has often been re ferred to as 'inflammatory COX' [2], It was detected in cells from inflammatory sites in animal models [3][4][5] and in the synovial tis sues of patients with rheumatoid arthritis [6], We have recently suggested that prostaglan din Ei, which may be generated via COX-2, was involved in plasma exudation in an in flammatory model [7], In addition, the ex pression of COX-2 was not detected in the kidney or the stomach even of rats suffer ing inflammation [3], These observations prompted the view that compounds having selectivity for COX-2 may become a new class of nonsteroidal anti-inflammatory drug (NSAID) exerting less harmful side effects, such as less irritation of the stomach mucosa and less renal toxicity [2], Most conventional NSAIDs are rather selective for COX-1 or are equipotent for both isoforms [8]. NS-398 is a prototype selective COX-2 inhibitor which shows far higher selectivity for COX-2 than for COX-1 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nimesulide, another COX-2-selective inhibitor [15], did not significantly suppress the PGE 2 production. As mentioned above, COX-2 is not detectable in stomachs isolated from normal control rats [24] and also in those isolated from rats injected with 1 mol/l NaCl solution (data not shown). All these results suggest that the PGE 2 released after injection of 1 mol/l NaCl solution may be produced via COX-1, as we previously suggested in Sprague-Dawley rats [16].…”
Section: Discussionmentioning
confidence: 50%
“…In addition to an inducible type of COX, namely COX-2, PLA 2 [22] and PGE synthase [23] are also known to be induced in response to various types of stimuli. COX-2 is not detectable in homogenate of whole stomachs isolated from normal control rats [24] and also in that isolated from rats injected with 1 mol/l NaCl solution (data not shown). Furthermore, the taurocholate-induced increase in PGE 2 release from the rat stomach depends on COX-1 [25].…”
Section: Discussionmentioning
confidence: 85%
“…In the case of swelling PGEs are thought to cause plasma exudation in a synergistic fashion with other mediators such as complement factor 5a [19]. Harada et al [20] also reported that the PGE 2 generated via COX-2 is involved in plasma exudation in inflammatory models. These observations prompted the view that compounds having selectivity for COX-2 and administered locally could have less systemic side-effects.…”
Section: Discussionmentioning
confidence: 99%